Investigation of technological parameters effect on metal removal during centrifugal rotary machining - Van Tho Nguyen; Eh. Eh. Tischenko; I. A. Panfilov; A. A. Mordovtsev (Advanced Engineering Research)
Introduction. The study results on the single interaction under the centrifugal rotary part machining in the abrasive discrete medium are presented. Simultaneously with the numerical simulation, experiments were carried out on a centrifugal-rotary unit, and the maximum depth of penetration into the surface of the part, the single-track sizes, metal removal in one blow of an abrasive granule, were investigated. The removal of metal from workpieces was investigateddepending on the processing modes, characteristics of the abrasive particle and the processed material.Materials and Methods. The dependences for determining the metal removal from workpieces (steels 45, copper Cu-OF, and aluminum alloy D16T) are taken into account depending on the grain size (N3) of abrasive particles. The process of a single interaction of an abrasive particle and the workpiece surface is considered within the framework of the dynamic contact problem of the elasticity theory. The authors have carried out finite element modeling of the considered structures in CAE ANSYS package.Results. The results of theoretical and experimental studies on the metal removal from workpieces depending on the grain size of abrasive particles are presented. The technique of their implementation, the tool and equipment used are described. The results of theoretical and experimental studies are compared. Their fine precision is established. Abrasive tools and processing modes are selected.Discussion and Conclusions. The dependences constructed in the work provide determining the rational values of the technological parameters of the centrifugal rotary machining (CRM) process. They can be used under designing the CRM processes. Therefore, time and financial resources can be saved to achieve the desired surface quality.